Academic fault lines : the rise of industry logic in public higher education - Gumport, Patricia J. (Johns Hopkins University Press, 2019)
"Gumport chronicles the rise of "industry logic," as a departure from "social institution logic," in public higher education in the latter twentieth century. Industry logic refers to colleges restructuring for financial efficiency and developing more ties with industry. Since the 1970s, increased public scrutiny and demands for accountability have pushed colleges to become more corporatized and privatized. Gumport's sociological analysis is grounded in data from nine in-depth case studies that span three sectors of public higher education"--